Belanja Online dan Gaya Hidup Mahasiswa Studi Kasus Semester 1 Fakultas Ekonimi dan Bisnis Universitas Negri Gorontalo - Valentina Monoarfa; Sri Rahmalia Saleh; Nanda Utuli; Susmiyati Talibana; Arya Makalalag; Mohamad Rizki Bau; Muhammad Rayhan Monoarfa (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
From this study shows that online shopping has become a lifestyle of students today, with the ease, convenience and wider accessibility compared to traditional shopping. With the advancement of information and communication technology that can make it easier for consumers to buy various products directly from home using digital devices such as cellphones, laptops and others. This study also covers the factors that influence consumers to shop online and understand the comparison Regarding people who have made online shopping transactions, people who often shop online / crazy about online shopping and its impact on religious law, then people who have never shopped online. The expected results so that we as consumers pay more attention when making online shopping transactions. Thus the study to determine the comparison and factors regarding online shopping at the faculty of economics and business.